Interventions to Improve Sexual Health in Iranian Cancer Patients: A Systematic Review - Masoud Bahrami; Ali Norouzi; Faramarz Kooshesh; Masoumeh Masoumy (Iranian Journal of Nursing and Midwifery Research)
Background: The sexual health of cancer patients may be impaired by cancer diagnosis, treatment-related complications. The goal of this systematic review is to describe the interventions used to improve sexual health in Iranian cancer patients. Materials and Methods: The following databases were searched: MEDLINE, Web of Science, Scopus, Cochrane Library, and Iranian databases (Magiran, SID, NoorMags), and gray literature from their inception until 21 December 2023. Keywords include sexual health, sexuality, sexual activity, sexual function, cancer, neoplasm, tumor, malignancy, and Iran. The reference lists of articles were also searched. Trials were included that compared psychosexual interventions in adults aged 18 years or over with a cancer diagnosis versus usual care and other controls. These trials were conducted in Iran and were results published in Persian or English journals and reported sexual outcomes as the main findings. Two review authors independently considered trials for inclusion in the review, assessed the risk of bias, and extracted data. Results: All studies (n = 291) were reviewed and 20 met the inclusion criteria. Most studies (n = 18) focused on breast cancer patients and were conducted in Tehran (n = 11). The majority of studies were psychosexual interventions leading to positive effects in aspects of sexual health, including body image, sexual function, sexual satisfaction, sexual self-esteem, sexual schemas, sexual quality of life, and sexual desire. Conclusions: The results showed that psychosexual interventions have been effective in improving the sexual health of cancer patients. Sexual health care should be an integral part of holistic, person-centered care for patients with cancer.